The user satisfaction of urban park: Case of trabzon eyof memorial park - Bayramoglu, E.; Demir, Sara (Parlar Scientific Publications, 2020)
Urban parks are open green spaces that can provide the physical and spiritual needs of the urban occupants in their leisure time and also improve the quality of urban life. These parks offer intense activity opportunities for the city users because of their location in city center and its immediate surroundings. The diversity of activities, usage density and accessibility to the area are the main important issues for the user satisfictation of urban parks. In this context, the aim of this study is to determine the user satisfaction of Eyof Memorial Park in Trabzon.To reach of this aim, it was applied two main stages. In the 1st stage; a questionnaire consisting of 15 questions in total was conducted in order to determine the sociodemographic situation, usage status and time of the user group. In the 2st stage; the factors effects on the users satisfaction and dissatisfaction were evaluated by 11 experts on the Likert attitude scale. As a result, 22 satisfaction and 14 dissatisfaction criteria were determined. Accordingly, the criteria of satisfaction and dissatisfaction are grouped under 3 main factors (Personal criteria (Fl), Social criteria (F2), natural and environmental impacts (F3). Consequently, it was determined 79.46% satisfaction rate and 47.83% dissatisfaction rate with 3,973 average value for Trabzon Eyof Memorial Park. The findings and methodology of this study may be an example for development of user satisfaction of urban parks in the developing countries. © 2020 Parlar Scientific Publications. All rights reserved.
Keywords: Eyof Memorial Park; Trabzon; Urban parks; User satisfaction